A STUDY OF ELECTRONIC STRUCTURE OF AZOBENZENE MOLECULE AND ITS DERIVATIVES - (NIM: 20207017), ELLIANAWATI
Azobenzene based of organic conjugate molecules have been known to have a large second order nonlinear optical property. With this property, the molecules have a promise potential to be developed into variety photonics devices, such as optical switching, optical memory, as well as grating. A variation of nonlinear property of the molecules can be controlled by choosing a suitable of donor-acceptor group that attached on both sides of azo dyes. Hence, the study of the molecular structure is important. Through this study, the correlation between molecular structure and its physical properties can be found. One of the important methods to analyze the information about molecular structure is UV/Vis spectroscopy. The information provided by this method is in form of the absorption spectra, which originate from electronics transition between energy level in electronics structure of the molecule. In order to interpret the UV/Vis spectra of the molecule, it is important to study the electronic structure of the molecule. In this thesis, the Huckel method has been used to investigate the electronic structure of an azobenzene organic molecule. This approach neglects the repulsive interaction between electrons. The spectra resulted from the calculation provided a good agreement with the experimental result. Therefore, this study can simplify the calculation of the electronic structure.